Sequential Injection Spectrophotometric Method for Determination Paracetamol in Pharmaceutical Formulations using N- bromosuccinimide and Methyl Orange as Oxidants - Khdeeja Jabbar Ali (Journal of Global Pharma Technology, 2019)
Sequential injection analysis (SIA) system is proposed for the determination of Paracetamol (PCT). PCT was determined by SIA based on the reaction between N-bromosuccinimide (NBS) and Methyl orange as  reagent in found  PCT in acid medium , yielding a red colour complex with absorption maximum at 507 nm., Under the optimum experimental conditions   such as the flow rate  and loading coil length  , the reaction coil length , hydrochloric acid  concentration, KBr concentration , the methyl orange concentration  and NBS concentration with both volume of mix PCT and volume Methyl orange, the determinable ranges were 1–10 mg /L, the detection limit was equal to 0.0135 mg /L, this technique is characterized by its  system was ease and speed, It was applied to the determination of PCT in different drug samples.Keywords: Sequential injection analysis (SIA) system, Paracetamol (PCT), N-bromosuccinimide (NBS).